A 12 Years Neonatal Mortality Rate and Its Predictors in Eastern Ethiopia. (June 2021) - Dheresa, Merga; Daraje, Gamachis
Introduction . Surviving and thriving of newborn is essential to ending extreme poverty. However, the surviving and thriving of new born is depends on where neonates are born. The true feature of neonatal mortality rate and trends is not well known in the study area. Thus, we aimed to estimate a neonatal mortality incidence in each year, and determine factors associated though pregnancy observation cohort study in Eastern Ethiopia. Methods . The study was conducted in Kersa Health Demographic Surveillance System (KHDSS) among 36 kebeles. We extracted all events (38 541 live birth and 776 neonatal death) occurred between January 1, 2008 and December 30, 2019. Neonatal mortality rate was presented by neonatal death per 1000 live birth with 95% confidence interval in each years, and trends of neonatal morality was described with line regression. Cox proportional regression model was used to assess predictors and presented with an adjusted hazard ratio (AHR) and 95% CI. Results . The estimated cumulative average of neonatal mortality rate in this study was 20.3 (95% CI: 18.9-21.8) per 1000 live births. The rate was decline with regression coefficient β = −1.60. Risk of neonatal death was found to be significantly associated with neonate born to mother living in rural Kersa (AHR = 5.31; 95% CI: 3.07-9.18), born to mother not receiving antenatal care (AHR = 1.43; 95% CI: 1.15-1.78), low birthweight (AHR = 2.59; 95% CI: 2.05-3.27), and preterm newborn (AHR = 12.10; 95% CI: 9.23-15.86). Conclusion . Neonatal mortality in the study site is far from reaching the national and global target goals.